Developmental Letter Position Dyslexia in Turkish, a Morphologically Rich and Orthographically Transparent Language - Güven, Selçuk; Friedmann, Naama (Frontiers in Psychology, 2019)
We present the first report of a specific type of developmental dyslexia in Turkish, letter position dyslexia(LPD). LPD affects the encoding of the letter position, leading to letter migrations within words. In a multiple case study of 24 Turkish-speaking children with developmental LPD, we examined in detail the characteristics of this dyslexia​ and explored its manifestation in Turkish. We used migratable words, in which a migration creates another existing word (e.g., signer-singer), which exposed the migration errors of the participants. In sharp contrast with the common assumption that dyslexics in transparent languages, including Turkish, do not make reading errors, we have shown that right stimuli can detect even up to 30% reading errors. The participants made migrations in reading aloud, comprehension, lexical decision, and same-different tasks, in both words and nonwords. This indicates that their deficit is in the orthographic-visual-analysis stage, a stage that precedes the orthographic-input-lexicon and is shared by the lexical and nonlexical routes. Their repetition of nonwords and migratable words was normal, indicating that their phonological output stages are intact. They did not make digit migrations in reading numbers, indicating that the orthographic-visual-analyzer deficit is orthographic-specific. The properties of Turkish allowed us to examine two issues that bear on the cognitive model of reading: consonant-consonant transpositions were far more frequent than consonant-vowel and vowel-vowel migrations. This indicates that the orthographic-visual analyzer already classifies letters into consonants and vowels, before or together with letter position encoding. Furthermore, Turkish is very rich morphologically, which allowed us to examine the effect of the morphological structure of the target word on migrations. We found that there was no morphological effect on migrations: morphologically complex words did not yield more(nor fewer) migrations than monomorphemic ones, migrations crossed morpheme boundaries and did not preserve the morphological structure of the target word. This suggests that morphological analysis follows the letter-position encoding stage.